(untitled) (Journal of Atomic and Molecular Sciences, 2016)
High-level ab initio calculations utilizing explicitly correlated multi-reference configuration interaction method (MRCI-F12), considering Davidson modification(Q), core-valence correlation correction(CV) and scalar relativistic correction(SR), were performed to compute the Born-Oppenheimer potential energy curve (PEC) of the ground state X^1Σ^+ of NaH. On the base of the PEC, we obtained vibrational and rotational energy levels information of the ground state X^1Σ^+. The vibrational and rotational spectroscopic constants of X^1Σ^+ were compared with the available experimental values. We also report rotation-vibration spectra of the ground state for the isotopes of NaH, NaD and NaT molecules. The equilibrium internuclear distances R_e and dissociation energies D_e were calculated to be 1.8865 Å and 15823.29cm^-1 for the ground state X^1Σ^+ of NaH, which are in good agreement with the experimental results of 1.8859 Å and 15815 ± 5cm^-1.